AKTIVITAS ANTIOKSIDAN DAN FLAVONOID EKSTRAK BIJI KURMA - Siti Warnasih; Diana Widiastuti; Uswatun Hasanah; Laksmi Ambarsari; Purwantiningsih Sugita (Universitas Pakuan, 2019)
Date seeds are waste from palm fruit processing that has not been utilized optimally. Date seeds contain flavonoids which are known to act as antioxidants. The aim of this study was to determine the antioxidant activity and flavonoid of methanol extract which was carried out by soxhletation and its fractionation results. Date seeds are made into simplicia, soxhlet extraction with methanol, then the methanol extract is fractionated in stages by liquid-liquid partition with n-hexane, ethyl acetate, and n-butanol. Each fraction and extract was determined by its antioxidant activity with the DPPH method and its flavonoid was determined by spectrophotometry. Ethyl acetate fraction has the strongest antioxidant activity with the lowest IC50 value, that is equal to 5.74 ± 0.05Î¼g/mL, followed by methanol extract of 9.55±0.53 Î¼g/mL, n-butanol fraction 19.73±0,58 Î¼g/mL, and n-hexane fraction of 289.59±10.52 Î¼g/mL, while the IC50 value for vitamin C as a positive control was 4.29±0.74 Î¼g/mL. The highest flavonoids were produced from ethyl acetate fractions which amounted to 1484.33 ± 161.47 mg Quercetin Equivalent (QE) / 100 g, followed respectively by methanol extract of 282.84±13.72 mg QE/100 g.